Antimony Resistance in Leishmania, Focusing on Experimental Research - Fakhri Jeddi; Renaud Piarroux; Charles Mary (Journal of Tropical Medicine)
Leishmaniases are parasitic diseases that spread in many countries with a prevalence of 12 million cases. There are few available treatments and antimonials are still of major importance in the therapeutic strategies used in most endemic regions. However, resistance toward these compounds has recently emerged in areas where the replacement of these drugs is mainly limited by the cost of alternative molecules. In this paper, we reviewed the studies carried out on antimonial resistance in Leishmania. Several common limitations of these works are presented before prevalent approaches to evidence antimonial resistance are related. Afterwards, phenotypic determination of resistance is described, then confronted to clinical outcome. Finally, we detail molecular mechanisms and targets involved in resistance and already identified in vitro within selected mutant strains or in clinical isolates.